Cytological criteria of differentiation of phyllodes tumor of the breast and fibroadenoma - О. G. Grigoruk (ABV-press, 2019)
The article is devoted to the determination of the cytological criteria of differentiation of fibroadenoma and phyllodes tumor. By means of multivariate analysis the 11 most informative cellular signs of fibroadenoma, juvenile fibroadenoma and benign phyllodes tumors were identified. According to the discriminant analysis, only 37.97 % of patients with benign phyllodes tumors are classified correctly, that indicates the difficulties of differentiation of these tumors. Some cellular signs of fibroadenoma, borderline and malignant phyllodes tumor allow to diagnose these forms of tumors.